Review Of Passenger Services on Board in Mengkapan – Telaga Punggur Tracking Based on Regulation Number 39 of 2015 - Rudy Sugiharto; Windi Nopriyanto; Fitria Cahyanti (IWJ : Inland Waterways Journal, 2019)
Mengkapan Ferry Port has a very important role in the effort to support economic develop Regulationent in the region Siak District, Riau Province. There are three tracks with four ships that served in the Mengkapan Ferry Port. One of these tracks connecting with Batam Island Riau Province is Mengkapan trajectory - Telaga Punggur served by KMP. Lome and KMP. Satria Pratama.Passenger service on board must conformwith regulation. Transportation number 39 2015, Chapter II, Article 4, for ferry transport service providers must provide the best service to the service user, The method used to analyze the existing problems is by comparison benchmarks contained in the regulation services with existing service conditions on board the ship on track Mengkapan - Telaga Punggur. Based on the analysis, it is known KMP. Lome and KMP. Satria Pratama for passenger service there are no health and safety officer, no special space for a wheelchair, does not provide wheelchair, does not provide a sticker with the number of complaints and the room temperature KMP. Satria Pratama more than 27 ° C is 34,55˚C. The conclusion that the conditions and criteria for passenger service on the boat on the track Mengkapan - Telaga Punggur there are not in accordance with the rules so that service providers should seek follow-up to meet the service in accordance with the regulations.